PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA PADA KARYAWAN DINAS PETERNAKAN DAN PERIKANAN KABUPATEN SITUBONDO DENGAN DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING - Safako, Bahjatus; Ediyanto, Ediyanto; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2024)
The era of globalization demands competition from all organizations or companies to compete with each other in order to compete for a position as a superior company. The aim of this research is to analyze and test the influence of organizational culture, organizational commitment and work motivation on the performance of ASN employees at the Livestock and Fisheries Service with Work Discipline as an intervening variable. This research is explanatory research. The population in this study were ASN employees of the Livestock and Fisheries Service. The sampling technique uses a saturated sample technique. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, organizational culture has a significant positive effect on work discipline. Organizational commitment has a positive but not significant effect on work discipline. Work motivation has a significantly positive effect on work discipline. Work discipline has a negative but not significant effect on performance. Organizational commitment has a significant effect. negative effect on Performance Work motivation has a significant positive effect on Performance Work discipline has a significant positive effect on Performance Work discipline has a significant positive effect on Performance through work Discipline Organizational Commitment has a significant positive effect on Performance through work Discipline Work motivation has a significant positive effect on Performance through work Discipline.